Efektivitas Kurikulum Pendidikan Islam dalam Meningkatkan Kecerdasaan Spiritual Siswa di MAN 1 Medan - Shifa Alya Nafisa; Aisyah Nazwa Listia; Cindy Aulia Lubis; Afrahul Fadhila Daulay (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study evaluates the effectiveness of the Islamic education curriculum in improving the spiritual intelligence of students at Madrasah Aliyah Negeri 1 Medan. The main problems faced include students from broken home families, lack of affection from parents, low empathy for students, and negative behaviors such as dating, smoking, and skipping school. The research method used is qualitative, with an observation, interview, and documentation approach. The purpose of the research is to identify the challenges faced and effective strategies to improve students' spiritual intelligence through the Islamic education curriculum. The results of the study show that despite various challenges, efforts such as joint dhikr activities, Yasin reading, motivation before lessons, and positive support from teachers can help strengthen students' spiritual intelligence. In conclusion, the effectiveness of the Islamic education curriculum is highly dependent on collaboration between teachers, schools, parents, and students. With good cooperation, challenges can be overcome and students' spiritual intelligence can be effectively improved.